SOCIO-ECOLOGICAL RESILIENCE (SER) STUDY FOR COASTAL VILLAGES TOWARDS TIDAL FLOODING - CASE STUDY: DESA TUNGKAL I, TANJUNG JABUNG BARAT REGENCY, JAMBI PROVINCE - Asri Hastari, Mulia
The complexity of the tidal flooding problem in coastal villages and its various causes are interrelated, including social and ecological aspects. An adaptive response is needed in coastal villages to cope with changes that occur through the ability of social-ecological systems to absorb disturbances and maintain function, structure, and identity so that they can be recovered through learning and adaptation or known as the concept of socio-ecological resilience (SER). In a resilient social-ecological system, the existence of disturbance is not only seen as destructive but also how disruption can create opportunities for development and innovation. Currently, efforts to build resilience only focus on one aspect of the problem so that it is unable to provide long-term security, especially in unexpected events that have the potential to cause long-term social and environmental problems. Therefore, a study on resilience is conducted that integrates socioecological aspects through the SER concept. This study aims to determine the socioecological resilience of Tungkal I Village against tidal flooding. SER study was carried out in Tungkal I Village, Tanjung Jabung Barat Regency, Jambi Province, as a coastal village prone to tidal flooding due to the influence of tides and increased by high rainfall and the potential for high waves. Resilience studies are carried out on social and ecological because the welfare of the two systems is interrelated. Social-Ecological Systems Framework (SESF) is used as a framework to understand the social-ecological system of Tungkal I Village as well as a basis in the formulation of indicators to determine SER. In the social system, indicators of resilience are summarized in the components of knowledge and learning, social capital, institutions, economy, and mangrove management. Whereas in the ecological system, indicators of resilience are summarized in the system characteristics component as well as landscape diversification and biodiversity. Furthermore, a tidal flooding hazard study was also conducted through indicators of the frequency of occurrence, the intensity of inundated areas, the magnitude of damage, and the height of inundation. Primary data collection was carried out through in-depth interviews with Tungkal I Village stakeholders as well as representatives of fishermen and coconut farmers through snowball results. Secondary data collection from official documents and scientific journals and observations of the study area were also carried out to complement the information. Data regarding tidal flooding hazard and resilience in social and ecologicaliv systems were analyzed through content analysis. The results showed that the Tungkal I Village tidal flooding was a threatening danger, as indicated by the high frequency of incidents, namely 24 times a year, the intensity of the floods was getting higher to 50-60 cm, more than 50% of the area was affected by tidal flooding and continues to increase, and tidal flooding has caused damage and losses. From the resilience analysis of the social and ecological systems, it is known that the social resilience of Tungkal I Village has not been formed, which is shown by the absence of good knowledge and learning about disasters, no strong community economy, no institutional support in disaster management, not all communities are involved actively involved in mangrove management and limited efforts to develop innovations in mangrove conservation. On the other hand, resilience has been formed in the ecological system, which is shown by the characteristics of the system which acts as a natural protector against tidal flooding while also contributing to the benefits of biodiversity for the community in the form of local food systems and livelihood opportunities. Resilience is important for social and ecological systems because the welfare of the two systems is interrelated so that the loss of resilience in both social and ecological systems makes the system vulnerable. Therefore, it can be concluded that Tungkal I village does not yet have socio-ecological resilience in cope tidal flooding. The analysis was then continued with a gap analysis, to formulate a strategy for increasing SER through ecosystembased adaptation strategies, including increasing community participation and developing innovation in mangrove ecosystem management, forming local organizations, and forging partnerships in disaster management, developing biodiversity-based local economies and increasing capacity public knowledge and understanding of the risks and efforts to reduce the risk of tidal flooding and ecosystem functions. This strategy is expected to help people adapt to changes and pressures caused by tidal flooding by using biodiversity while maintaining the function of the mangrove ecosystem as a natural protector from the dangers of tidal flooding